PERAMPANEL (FYCOMPA) FOR TREATMENT OF EPILEPSY (EXPERIENCE OF THE SVT. LUKA'S INSTITUTE OF CHILD NEUROLOGY AND EPILEPSY) - K. Yu. Mukhin; O. A. Pylaeva (Русский журнал детской неврологии)
Perampanel (Fycompa, Eisai LLC) is the most recent antiepileptic drug registered for application for additional therapy of patients of 12 y.o. and older with focal and secondary generalized seizures. Perampanel was licensed in the USA and European countries in 2012; it was registered in 2013 and entered the pharmaceutical market of Russia in 2014. Perampanel has a fundamentally different mechanism of antiepileptic action, different from other antiepileptic drugs. Perampanel is a powerful highly selective noncompetitive inhibitor of ionotropic AMPA receptors of postsynaptic membranes of neurons on level of the neocortex and the hippocampus. Efficacy and tolerability of perampanel with resistant focal seizures were proved in clinical studies of the III phase. Randomized placebo controlled studies of additional therapy with perampanel demonstrated the fact that intake of the drug in the dosage of 4 to 12 mg/day, which validly decreases the frequency of focal seizures of patients with pharmacoresistant epilepsy with favorable indicators of safety and tolerability. Open observational studies as well as long-term therapy studies also demonstrated favorable indicators of efficacy and safety with long-term treatment (up to 3 years) and long-term maintenance of therapeutic effect. The objective of the evaluation was study of efficacy and tolerability of perampanel (Fycompa) for additional therapy of patients with resistant forms of epilepsy. The study included 12 patients (6 males and 6 females) at the age of 3 to 37 y.o. with the intake of Fycompa with the period of follow-up study of over 6 months. All patients suffered from severe resistant forms of epilepsy (6 cases are genetic diseases, 6 cases are symptomatic focal epilepsy). Efficacy and good tolerability of Fycompa were marked. In general, decreasing of duration and/or severity of seizures was marked in 83% of cases. No serious side effects were registered. The authors made the conclusion of favorable prospectives of intake of Fycompa in various populations of patients that suffer from epilepsy.